Gender Equity in Bimanese Muslim Society from Islamic Perspectives - Nurdin, Nurdin (POLITEA, 2022)
Bimanese ethnic is the genealogies of specific ethnic in the eastern part of Sumbawa Island who was strongly influenced by Islamic teaching in their daily basis, including family life. They immensely uphold Islamic tradition in their everyday life, and their concept of gender equity is rooted from Islamic teaching and tradition. Therefore, this article will address the concept of gender equity in Islamic perspective as well as its implementations in Bimanese culture as the construction of Islamic teaching and tradition in forming everyday life of Muslim society in Bima. This research used a descriptive-qualitative method. Primary data is collected from literature studies including journals, theses/dissertation, and books related to gender equality issues in general and gender order in Bimanese society. The data were then analyzed descriptively and qualitatively. This research found that Islam strongly upholds gender equality in its normative teaching based on the interpretation of modern Muslim scholars, and the implementation of gender equality in Islamic perspective is also deeply rooted in Bimanese ethnic cultures even though it is not practiced well in their everyday life of family life in Bima nowadays.